Humanitarization of University and Social Engagement Mission - O. V. Zinevich; T. A. Balmasova (Высшее образование в России)
The paper focuses on substantiating the institutional significance of the humanitarian component of University education and demonstrating opportunities for its implementation through non-profit activities of the University community. Transition to the new technological order accentuates the relevance of new personal and communicative competencies formed on the basis of education in humanities. Humanitarization is a priority task, which is reflected in the University education practices in the United States and European countries. The idea of upbringing a humanitarianly educated and humanitarianly oriented personality is declared in the discourses of the world leading Universities’ missions, whose activities are aimed at achieving public good for the society and its sustainable development. Russian documents and discussions on higher education emphasize the importance of humanitarization, but in practice, the humanitarian component in Russian universities is clearly being underestimated. In our opinion, this is due to the fact that humanitarization means mainly the strengthening of the cognitive element of University programs – the expansion of humanitarian specialties and humanitarian courses, but socially oriented University practices are not taken into account. Meanwhile, humanitarization includes both the translation of humanitarian knowledge and values – the strategic goals of the development of society, the state, the region, and the activity-based approbation of the knowledge gained in extra-curricular practices.Humanitarization of higher education is considered in the article from the standpoint of social and philosophical analysis, within the ontological aspect as a mode of being of an institutionally organized human activity on knowledge production and translation, which has closely been expressed in creating University 3.0, as well as in the idea and discourse of the third mission of University. The third mission sufficiently strengthens its emphasis on the anthropological and social function – orientation of University activities towards the genesis of a creative personality and the increased good for society. The goal of achieving the good is explicitly present in those social practices that are aimed at participating in the life of society without direct commercial gain and is implemented outside the University. The article examines the main types of socio-humanitarian practices in universities in Western countries.